Five Facets for Effective English Language Teaching - Ghimire, Nani Babu (Journal of NELTA Gandaki, 2019)
Effective English language teaching (ELT) is strongly related to dynamic teachers and creative learners as it enhances students’ long lasting learning process. Students learn the taught matters successfully if the classroom is handled effectively focusing on child centered pedagogy with the use of modern information communication technology (ICT). The objective of this paper is to look at the different facets for effective ELT and to give some pedagogical suggestions for English language teachers to increase the effectiveness in ELT. The articles/papers, researches and books written on effective ELT found in electronic sources are studied/overviewed the study. It shows that an effective ELT includes qualified, dynamic and devoted teachers with socio-affective skills, pedagogical and subject matter knowledge, active and creative students, use of sufficient and practical teaching learning materials, proper use of modern equipment and technology, and multiliteracy pedagogy focusing on the cultural diversity of the learners for better ELT.